Economic models for new industrializing countries in comparative perspective - Ralph Wrobel (OrdnungsPolitisches Portal (OPO), 2013)
The last decades are characterized more and more by the catching-up of former communist and developing countries especially in Central and Eastern Europe as well as in East Asia. But which economic system is able to develop an economic successful catching-up combined with human development and poverty reduction? In this paper the author argues that especially New Industrializing Countries (NICs) can learn a lot from developed market economies, not only in the positive sense but also from their mistakes. NICs are already quite developed and reached a level of functioning institutions which allow focussing on developed role models. Therefore, in this paper first catching-up strategies of Less Developed Countries (LDCs) and NICs in the past are described briefly. Then, common experiences from OECD countries and different role models are discussed. As possible role models for NICs five country groups were established: (1) Anglo-Saxon Free Market Economy, (2) Nordic Welfare State, (3) Social Market Economy, (4) Mediterranean Capitalism, and (5) Asian Capi-talism. As can be shown, emerging economies can use the experiences of these countries to improve their catching-up strategies. Therefore, advantages and disadvantages of the role models are discussed in comparative perspective. It results, that no single peak economy exists. But the role models can give political deciders an impression which model may be helpful to find adaptive institutions for the own catch-ing-up process.
Keywords: 330; New Industrializing Countries; Catching-up Strategies; Varieties of Capitalism